Switching from omalizumab to mepolizumab: real-life experience from Southern Italy. (June 2020) - Carpagnano, Giovanna Elisiana; Pelaia, Corrado; D'Amato, Maria; Crimi, Nunzio; Scichilone, Nicola; Scioscia, Giulia; Resta, Onofrio; Calabrese, Cecilia; Pelaia, Girolamo; Quarato, Carla Maria Irene; Foschino Barbaro, Maria Pia
Background: Current availability of several biologic treatments for severe asthma makes it possible to choose the most appropriate for each patient. Sometimes a good percentage of patients with severe asthma may be eligible for biologics that target either the allergic phenotype or the eosinophilic one, but not all respond to that selected as first choice. The aim of our real-life study was to assess whether, for patients with severe eosinophilic allergic asthma, not previously controlled by the anti-IgE omalizumab, the shift to another biologic targeting interleukin-5, such as mepolizumab, may represent a good therapeutic choice. Methods: A total of 41 consecutive patients with severe, persistent allergic, eosinophilic asthma, uncontrolled despite treatment with omalizumab, were enrolled in seven certified Clinical Respiratory Units of Southern Italy (Catania, Catanzaro, Foggia, Bari, Palermo, and two University Respiratory Units of Naples) and shifted to mepolizumab without a wash-out period. Data at baseline, after at least 12 months of therapy with omalizumab, and after at least 12 months of treatment with mepolizumab were collected. Results: After at least 12 months of therapy with mepolizumab, patients experienced a significant decrease in the number of exacerbations/year (5.8 ± 1.8 versus 0.7 ± 0.9, p  < 0.0001), an increment of asthma control test score (12 ± 2.7 versus 21.9 ± 2.7, p  < 0.0001), an increase in pre-bronchodilator forced expiratory volume in 1 s (1.56 ± 0.45 l versus 1.86 ± 0.52 l, p  < 0.0001), and a reduction of blood eosinophils (584 ± 196 cells/µl versus 82 ± 56 cells/µl, p  < 0.0001). The percentage of patients who were dependent on corticosteroids significantly decreased from 46% at baseline to 5% during treatment with mepolizumab. Conclusion: Results of our real-life multicentric experience confirms that the shift to mepolizumab could be a good therapeutic strategy in severe eosinophilic allergic asthma not previously controlled by omalizumab. The reviews of this paper are available via the supplemental material section.